Discourse and religious doctrine: Professional social work and the moral regulation of the body in Roman Catholic Ireland - Flynn, Susan (My University, 2022)
The moral and practical regulation of sexuality and associated risk has been traditionally bound by Catholic religious doctrine in the Republic of Ireland. Over the last century, however, the emergence of professional social work as a state risk management strategy around sexuality is evident. This tallies with the disrepute of the Church following high-profile abuse scandals and publicized tragedies tied to institutional segregation. This paper presents theoretically informed critical commentary, through uptake of the Foucauldian notion of discourse. It concludes that critique of the regulation of sexuality, should be qualified on three counts. Firstly, tensions between Catholicism and social work remain. Secondly, wariness toward the operation of power is requisite. Thirdly, both that which is said, and unsaid, enlightens present debates.
PUBLISHED
Keywords: Sexuality; Religion; Ireland; Social work; Catholic